Mutual Shaping in Swarm Robotics: User Studies in Fire and Rescue, Storage Organization, and Bridge Inspection - Carrillo-Zapata, Daniel; Milner, Emma; Hird, Julian; Tzoumas, Georgios; Vardanega, Paul J.; Sooriyabandara, Mahesh; Giuliani, Manuel; Winfield, Alan F. T.; Hauert, Sabine (Frontiers in Robotics and AI, 2020)
Many real-world applications have been suggested in the swarm robotics literature. However, there is a general lack of understanding of what needs to be done for robot swarms to be useful and trusted by users in reality. This paper aims to investigate user perception of robot swarms in the workplace, and inform design principles for the deployment of future swarms in real-world applications. Three {qualitative} studies with a total of 37 participants were done across three sectors: fire & rescue, storage organisation, and bridge inspection. Each study examined the users' perceptions using {focus groups and interviews}. In this paper, we describe our findings regarding: the current processes and tools used in these professions and their main challenges; attitudes towards robot swarms assisting them; and the requirements that would encourage them to use robot swarms. We found that there was a generally positive reaction to robot swarms for information gathering and automation of simple processes. Furthermore, a human in the loop is preferred when it comes to decision making. {Recommendations to increase trust and acceptance are related to} transparency, accountability, safety, reliability, ease of maintenance and ease of use. Finally, we found that mutual shaping, {a methodology to create a bidirectional relationship between users and technology developers to incorporate societal choices in all stages of research and development}, is a valid approach to increase knowledge and acceptance of swarm robotics. This paper contributes to the creation of such a culture of mutual shaping between researchers and users, towards increasing the chances of a successful deployment of robot swarms in the physical realm.